Mitragyna speciosa: Opioid Addiction Treatment and Risk of Use - Endang Lukitaningsih; Nanang Fakhrudin; Azka Muhammad Rusydan (Universitas Sebelas Maret, 2022)
Kratom (Mitragyna speciosa (Korth.) Havil.) is a plant that originated from the rainforest in Southeast Asia, mainly grows in Thailand, Malaysia, and Indonesia. Kratom has been used traditionally as an herbal remedy for the treatment of various illnesses. Kratom gained notoriety due to its potential as an analgesic, opiate withdrawal treatment, anxiolytic, antidepressant, and antidiabetic with an unclear risk of addiction and toxicity fueled by a false sense of security due to its identity as a member of the coffee family. This article is a narrative review on kratom to highlight its pharmacological and toxicological properties, and the analytical method of Kratom, especially its potential as an opioid withdrawal therapy and its risk of abuse.